Hemodynamic effects and tolerance of dobutamine for myocardial dysfunction during septic shock: An observational multicenter prospective echocardiographic study - Razazi, Keyvan; Labbé, Vincent; Laine, Laurent; Bedet, Alexandre; Carteaux, Guillaume; de Prost, Nicolas; Boissier, Florence; Bagate, Francois; Mekontso Dessap, Armand (Frontiers in Cardiovascular Medicine, 2022)
Background The role of dobutamine during septic shock resuscitation is still controversial. Methods The aim of this prospective multicentre study was to comprehensively characterize the hemodynamic response of septic shock patients with systolic myocardial dysfunction to incremental doses of dobutamine (0, 5, 10, and 15 μg/kg/min). Results Thirty two patients were included in three centers. Dobutamine significantly increased contractility indices of both ventricles [crude and afterload-adjusted left ventricular (LV) ejection fraction, global LV longitudinal peak systolic strain, tissue Doppler peak systolic wave at mitral and tricuspid lateral annulus, and tricuspid annular plane excursion) as well as global function indices (stroke volume and cardiac index) and diastolic function (increased e' and decreased E/e' ratio at lateral mitral annulus). Dobutamine also induced a significant decrease in arterial pressure and cardiac afterload indices (effective arterial elastance, systemic vascular resistance and diastolic shock index). Oxygen transport, oxygen consumption and carbon dioxide production all increased with dobutamine, without change in the respiratory quotient or lactate. Dobutamine was discontinued for poor tolerance in a majority of patients (n = 21, 66%) at any dose and half of patients (n = 15, 47%) at low-dose (5 μg/kg/min). Poor tolerance to low-dose dobutamine was more frequent in case of acidosis, was associated with lower vasopressor-free days and survival at day-14. Conclusion In patients with septic myocardial dysfunction, dobutamine induced an overall improvement of echocardiographic parameters of diastolic and systolic function, but was poorly tolerated in nearly two thirds of patients, with worsening vasoplegia. Patients with severe acidosis seemed to have a worse response to dobutamine.